Preparation of Hollow Silica Nanoparticles Using Fluorinated Surfactant and Fluorocarbon Solvents - Phung, Thanh Khoa; Giang, Ha N.; Vu, Khanh B. (JST: Engineering And Technology For Sustainable Development, 2021)
In this study, we used a new class of fluorinated surfactant as a soft template for the preparation of the hollow silica nanoparticles. The size of the hollow silica nanoparticles was enlarged by incorporating a variety of swelling agents (perfluorodecalin, perfluorotributylamine, perfluorooctane, and perfluorooctyl bromide) into the cores of the micelles of the fluorinated surfactant. However, once we used the perfluorinated acids (perfluorooctadecanoic acid and perfluorodecanoic acid) as swelling agents, the structure of silica nanoparticles is solid without the formation of hollow voids. The TEM analysis combined with copper elemental mapping of the hollow silica loaded with copper hexadecafluorophthalocyanine indicated that the cores of the hollow silica nanoparticles are hydrophobic. The formation mechanism of the hollow silica nanoparticles is similar to that prepared by hydrocarbon surfactant/hydrocarbon, which was supported by the zeta potential measurements. The prepared hollow silica nanoparticles had the type IV isotherm with the H3 hysteresis loop.